DHARUR-6: A Custard Apple variety for cultivation in Maharashtra (Indian Journal of Arid Horticulture, 2016)
Custard apple, Annona squamosa L., commonly known by various names such as sitaphal, sita palam, sharifa, sita pazham, sita phalmu, katal, ata, and sweet sop depending on the region, is a fruit recognized for its sweet and delicate flesh. Known as a delicacy of dry regions, custard apple's pulp is noted for its pleasant flavor and texture, being sweet with a slight acidity. This fruit is rich in carbohydrates, mainly sugars, as well as protein, calcium, phosphorus, and iron. Primarily consumed as a dessert fruit, custard apple pulp is often mixed with milk to prepare a drink or incorporated into ice cream. In Maharashtra, custard apple is cultivated across an area of 60,000 hectares in districts such as Pune, Beed, Aurangabad, Nanded, Dhule, Jalgaon, Nandurbar, Osmanabad, Latur, Ahmednagar, Solapur, Bhandara, and Wardha. The Balaghat hills of Marathwada are particularly famous for the natural occurrence of custard apple.
Keywords: Aurangabad; Bhandara; ice cream